A 9% power efficiency 121-to-137GHz phase-controlled push-push frequency quadrupler in 0.13μm SiGe BiCMOS - Wang, Yong (2013)
High-data-rate short-range communication and image systems beyond 100GHz impose crucial requirements on signal sources, demanding superior purity and stability. Using frequency multipliers with high efficiency and multiplication factor to generate the Nth harmonic signal that is phase-locked by a PLL at the fundamental frequency provides an alternative solution. The desired signal in an active frequency multiplier can be generated using Class B/C amplifiers, where a half-wave signal containing all harmonics is first created and then filtered to remove the undesired harmonic components [1]. Another approach is to apply the same signal to both the IF and RF ports of a mixer to construct a doubler followed by cascading to form the quadrupler [3]. The linear superposition (LS) technique that superimposes four phase-shifted half-waves of 0°, 90°, 180°, and 270° is another popular scheme [5]. For multipliers with high multiplication factors, these prior techniques may offer very low power efficiency (η). Quadrupler cores based on Class B/C amplifiers, mixers, or the LS technique had been reported with η of 0.9% [1], 0.04% [3] and 0.0002% [5], respectively. Therefore, instead of improving the η of the multiplier cores, the design of the subsequent amplifiers after the multiplier to boost the η and output power has become a popular approach. We have substantially enhanced the η of a frequency quadrupler core using a phase-controlled push-push (PCPP) technique to directly synthesize the 4th harmonic. We noted that in an ideal situation, the proposed quadrupler circuit is able to generate almost no other harmonics, attaining an η of 50%. In this paper, we present a 121-to-137GHz frequency quadrupler based on a 0.13μm SiGe BiCMOS process. For the purpose of measurement, a balun coupled with buffers to provide the differential signals is also designed. The DC power con- umptions of the quadrupler core and input buffers are 6.4mW and 28.8mW, respectively. Our demonstrated quadrupler core is able to achieve 9% (1.6% including input buffers) power efficiency at 1.6V, with a -2.4dBm output signal.